2020
DOI: 10.3390/su12093670
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Economic Sustainability of Table Grape Production in Italy

Abstract: In recent years, the environmental sustainability of agri-food systems has become a crucial issue. Agri-food firms are increasingly concerned with the implementation of viable environmentally friendly production processes. The environmental impacts of the table grape sector, as well as other fresh and not transformed food products, involve mainly the farming phase rather than the subsequent conditioning, transportation, packaging, and distribution phases. The purpose of this study was to assess the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
2
20
0
1
Order By: Relevance
“…Looking at the process impacts (Figure 3a), irrigation and fertilizers are the primary causes, followed by fieldwork operations and land occupation. This confirms the findings of previous studies on open-field tomatoes [38], table grapes [39], and artichokes [40], which identified irrigation and fertilization as the main environmental burdens. Irrigation as a process accounted for 46% of EEC for tomatoes, 24% for grapes, and 20% for Looking at the process impacts (Figure 3a), irrigation and fertilizers are the primary causes, followed by fieldwork operations and land occupation.…”
Section: What Is the Size Of External Environmental Costs Of Crops Irrigated With Reclaimed Water?supporting
confidence: 91%
“…Looking at the process impacts (Figure 3a), irrigation and fertilizers are the primary causes, followed by fieldwork operations and land occupation. This confirms the findings of previous studies on open-field tomatoes [38], table grapes [39], and artichokes [40], which identified irrigation and fertilization as the main environmental burdens. Irrigation as a process accounted for 46% of EEC for tomatoes, 24% for grapes, and 20% for Looking at the process impacts (Figure 3a), irrigation and fertilizers are the primary causes, followed by fieldwork operations and land occupation.…”
Section: What Is the Size Of External Environmental Costs Of Crops Irrigated With Reclaimed Water?supporting
confidence: 91%
“…where IC represents the investment costs, CF n is the annual cash flow generated, is obtained by subtracting total output operational costs, and r is the discount rate. Different baseline discount rates, as advised by the European Commission [42], were set (ranging from 1% to 5%), according to recent studies in which tree crop plantation investments were analyzed [42][43][44][45][46][47].…”
Section: Economic Assessmentmentioning
confidence: 99%
“…Indeed, farmers' special skills have contributed to the lack of livelihood in Sanjiangyuan National Park. We suggest two ways to achieve this goal: to use the comprehensive regional development to help farmers increase their income and popularize the measures of farmers' vocational skills training to increase the efficiency and income of farmers' vocational skills production [45].…”
Section: The Awareness Of Policies and Naturalmentioning
confidence: 99%